2005
DOI: 10.1111/j.1743-6109.2005.00081_1.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Erectogenic Pharmacotherapy Regimen Following Radical Prostatectomy Improves Recovery of Spontaneous Erectile Function

Abstract: Purpose It has been suggested that postradical prostatectomy (RP) erectile function outcomes are improved by early use of erectogenic medications. This analysis was designed to assess the ability of a post-RP vasoactive drug program to improve long-term spontaneous erectile function. Methods Men with functional preoperative erections who underwent RP were challenged early postoperatively with oral sildenafil. Nonresponders we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 27 publications
4
121
0
1
Order By: Relevance
“…Early penile rehabilitation can significantly improve the rate of postoperative spontaneous erections and sexual QoL, and administration of a PDEI-5 such as sildenafil can help to enhance rigidity. [7][8][9] According to a literature review, the efficacy of sildenafil ranges from 14 to 53%, but this range can be extended to 14-85% on switching to ICI. 10,11 Penile rehabilitation should be discussed with all patients, regardless of their sexual motivation, and initiated promptly after RP.…”
Section: Discussionmentioning
confidence: 99%
“…Early penile rehabilitation can significantly improve the rate of postoperative spontaneous erections and sexual QoL, and administration of a PDEI-5 such as sildenafil can help to enhance rigidity. [7][8][9] According to a literature review, the efficacy of sildenafil ranges from 14 to 53%, but this range can be extended to 14-85% on switching to ICI. 10,11 Penile rehabilitation should be discussed with all patients, regardless of their sexual motivation, and initiated promptly after RP.…”
Section: Discussionmentioning
confidence: 99%
“…43 Penile rehabilitation after nerve-sparing radical prostatectomy: Clinical evidence Despite all the evidence in favor of chronic treatment with PDE5-I, only a few trials have assessed the role of penile rehabilitation in men who underwent RP. [46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
“…[46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP. In this context, the prophylactic administration of a vacuum constriction device also has been proposed recently as an early penile rehabilitation approach aimed at promoting adequate cavernosal oxygenation and, thus, preventing penile fibrosis after surgery.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
See 1 more Smart Citation
“…Treated men also had a much higher response to sildenafil after 18 months, as well as higher IIEF-EF domain scores. 38 It is noted that the use of needles dissuades men from strict ICI rehabilitation protocols, as the attrition rate is quite high several months into treatment. 39 Intraurethral prostaglandins as a rehabilitation agent has been tested in the form of the Medicated Urethral System for Erection (MUSE; Vivus Inc., Mountain View, CA, USA).…”
Section: Penile Rehabilitationmentioning
confidence: 99%